(untitled) (Research, Society and Development, 2020)
This study aimed to assess health-related physical fitness in students practicing collective gymnastics. This is a field research carried out with 141 teenagers practicing collective gymnastics at the Federal Institute of Ceará. Health-related physical fitness was assessed by collecting anthropometric data, body composition, levels of flexibility, abdominal resistance and aerobic fitness, before and after the period of practical classes. The results showed a 5.2% weight reduction, increased levels of flexibility (26.32 ± 10.09 vs. 28.62 ± 9.29), abdominal resistance (22.76 ± 8.22 vs. 29, 41 ± 7.82) and aerobic fitness (465.34 ± 40.71 vs. 755.58 ± 70.12). In conclusion, it can be identified that the practice of collective gymnastics increased the musculoskeletal physical fitness and physical fitness for cardiovascular health, however, it did not reach the healthy zone of aerobic fitness.